(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Bearing in mind that the analyses of Judita Šalgo’s novel Journey to Birobidzhan typically deal with the vision of a feminist utopia, this study centers on alternative artistic visions (neither male nor female). A less interpreted part of the novel – ”The Original sin of Nenad Mitrov” will be analyzed and show parallels between conclusions that Linda Hutcheon made on poetics of postmodernism and poetics of the novel (implicit and explicit). This paper views the striving for the indefinable and elusive land of Birobidzhan (given through the Jewish myth of homeland) as reinterpretation and destabilization of one of the most common literary motifs – the quest motif. The motif relates to the vision of poetics and art in the postmodern world of the novel that lacks paradigms or coherence.